Odpowiedź :
a) 3*(-3)-2*(-4)= -9+8= -1
b) -3*(-1/2 do potęgi 2)+3*(-1/2)+1=3*(1/2 do potęgi 2)+3*(-1/2)+1=3*1/4-3*1/2+1=3*1/4-3/2+1=3/4-3/2+1=1/4
c) 2*(-2 do potęgi 2)-(-1/4)+(-2 do potęgi 3)=-2*2 do potęgi 2 -(-1/4) +(-2 do potęgi 3)=-2 do potęgi 3 +1/4+(-2 do potęgi 3)=-2 do potęgi 3 +1/4-2 do potęgi 3=-2*2 do potęgi 3 +1/4=-2 do potęgi 4 +1/4=-16+1/4=-63/4= 15 i 3/4
d) -(-2 do potęgi 3)-(-1/5 do potęgi 2)-5*(-2/5)+10=2 do potęgi 3 +(1/5) do potęgi 2 +5*2/5+10=2 do potęgi 3 +(1/5) do potęgi 2 +2+10=8+1/25+2+10=20+1/25=501/25=20 i 1/25
e) (-1+2/minus 1)*(- 2/minus 1- (-1 do potęgi 2)=(--2)*(-(-2)-(-1))=-3(2+1)=-3*3=-9
sory że tak haotycznie ale próbowałam zrobić to dokładnie krok po kroku i mam nadzieję że jest dobrze